The use of Proverbs in Teaching Languages (In the Comparative Object of Russian and Uzbek) - Bekmukhamedova Nargiz Islamovna (Researchparks Publishing, 2021)
Consideration of the language in the universal and nationally specific aspects as one of the tasks of modern linguistics. Zoonyms in the paremias of the Russian and Uzbek languages are an original linguistic layer that reveals the specifics of the worldview of culture carriers. Any language, going through the regular stages of its development over hundreds and thousands of years, invariably becomes overgrown with inclusions that came into it from other dialects. Naturally, this happened with the Uzbek language, whose speakers lived at the intersection of many civilizations, contacted and continue to interact with representatives of hundreds of languages and dozens of language groups.